2020
DOI: 10.3390/jfmk5040082
|View full text |Cite
|
Sign up to set email alerts
|

Nordic Walking and Free Walking Improve the Quality of Life, Cognitive Function, and Depressive Symptoms in Individuals with Parkinson’s Disease: A Randomized Clinical Trial

Abstract: Nordic walking’s (NW) degree of effectiveness regarding health-related parameters in people with Parkinson’s Disease (PD) is a subject of debate. While NW seems to improve functionality, a clear non-motor benefit has not been demonstrated. The aim of this randomized controlled trial was to compare the effects of 9-week NW and free walking (FW) training programs on quality of life, cognitive function, and depressive symptoms in individuals with PD. Thirty-three people with PD, (Hoehn and Yahr 1–4) were randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Disease duration was informed in 11 studies. In six investigations, participants had been living with the disease between 5.1 and 7.8 years (Cugusi et al, 2015; Ebersbach et al, 2010, 2014; Granziera et al, 2021; Monteiro et al, 2017; Passos‐Monteiro et al, 2020; Wróblewska et al, 2019). Szefler‐Derela et al (2020), reported the information as a median (NW group: 6 years; Control Group: 5 years), minimum and maximum (NW group: 3–18 years; Control Group: 2–14 years).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Disease duration was informed in 11 studies. In six investigations, participants had been living with the disease between 5.1 and 7.8 years (Cugusi et al, 2015; Ebersbach et al, 2010, 2014; Granziera et al, 2021; Monteiro et al, 2017; Passos‐Monteiro et al, 2020; Wróblewska et al, 2019). Szefler‐Derela et al (2020), reported the information as a median (NW group: 6 years; Control Group: 5 years), minimum and maximum (NW group: 3–18 years; Control Group: 2–14 years).…”
Section: Resultsmentioning
confidence: 99%
“…Methodological quality is shown in Table 1, being good in eight RCTs (Antunes Marques et al, 2019; Bang & Shin, 2017; Ebersbach et al, 2010, 2014; Franzoni et al, 2018; Granziera et al, 2021; Passos‐Monteiro et al, 2020; Reuter et al, 2011) and fair in four studies (Cugusi et al, 2015; Monteiro et al, 2017; Wróblewska et al, 2019) All the trials accomplished items 1 (random allocation), 9 (between‐group comparison) and 10 (point estimates and variability). Items 3 (baseline comparability), 7 (adequate follow‐up) and 6 (blinding assessors) were met by 92%, 83% and 75% of the included studies respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most studied outcomes are quality of life, motor and disease staging, physical mobility, and depressive symptoms [5,12,14,30]. Few studies have studied biomechanical and balance outcomes, especially on anticipatory postural adjustments and the relationship with falls.…”
Section: Brief Literature Review On Evaluation and Training Protocols...mentioning
confidence: 99%